Effectiveness and Safety of a Prolonged Hemodynamic Support by the IVAC2L System in Healthy and Cardiogenic Shock Pigs - Delmas, Clément; Porterie, Jean; Jourdan, Géraldine; Lezoualc'h, Frank; Arnaud, Romain; Brun, Stéphanie; Cavalerie, Hugo; Blanc, Grégoire; Marcheix, Bertrand; Lairez, Olivier; Verwaerde, Patrick; Mialet-Perez, Jeanne (Frontiers in Cardiovascular Medicine, 2022)
Background Mechanical circulatory supports are used in case of cardiogenic shock (CS) refractory to conventional therapy. Several devices can be employed, but are limited by their availability, benefit risk-ratio, and/or cost. Aims To investigate the feasibility, safety, and effectiveness of a long-term support by a new available device (IVAC2L) in pigs. Methods Experiments were carried out in male pigs, divided into healthy (n = 6) or ischemic CS (n = 4) groups for a median support time of 34 and 12 h, respectively. IVAC2L was implanted under fluoroscopic and TTE guidance under general anesthesia. CS was induced by surgical ligation of the left anterior descending artery. An ipsilateral lower limb reperfusion was created with the Solopath® system. Reperfusion was started after 1 h of support in healthy pigs and upon IVAC2L insertion in CS pigs. Hemodynamic and biological parameters were monitored before and during the whole period of support in each group. Results Occurrence of an ipsilateral lower limb ischemia was systematic in healthy and CS pigs in a few minutes after IVAC2L implantation, and could be reversed by the arterial reperfusion, as demonstrated by distal transcutaneous pressure in oxygen (TcPO2) and lactate normalization. IVAC2L support decreased pulmonary capillary wedge pressure (PCWP) (15.3 ± 0.3 vs. 7.5 ± 0.9 mmHg, p < 0.001), increased systolic blood pressure (SBP) (70 ± 4.5 vs. 101.3 ± 3.1 mmHg, p < 0.01), and cardiac output (CO) (4.0 ± 0.3 vs. 5.2 ± 0.6 l/min, p < 0.05) in CS pigs; at CS onset and after 12 h of support, without effects on heart rate or pulmonary artery pressure (PAP). Non-sustained ventricular arrhythmias were frequent at implantation (50%). A non-significant hemolysis was observed under support in CS pigs. Bleedings were frequent at the insertion and/or operating sites (30%). Conclusion Long-term support by IVAC2L is feasible and associated with a significant hemodynamic improvement in a porcine model. These preclinical data open the door for a study of IVAC2L in human ischemic CS, keeping in mind the need for systematic reperfusion of the lower limb and the associated risk of bleeding.